Acute relationships between mental health and cognitive function during the COVID-19 pandemic: Longitudinal evidence from middle-aged and older US adults - Lindsay C. Kobayashi; Brendan Q. O'Shea; Carly Joseph; Jessica M. Finlay (Elsevier, 2022)
Background: The acute impacts of COVID-19-related mental health concerns on cognitive function among middle-aged and older adults are unknown. We investigated whether between-person (BP) differences and within-person (WP) changes in loneliness, anxiety, and worry about COVID-19 were related to cognitive function and abilities in a longitudinal cohort of middle-aged and older United States (US) adults over a nine-month period during the COVID-19 pandemic. Methods: Data were from bimonthly questionnaires in the nationwide COVID-19 Coping Study from August/September 2020 through April/May 2021 (N = 2262 adults aged ≥55). Loneliness was assessed with the 3-item UCLA Loneliness Scale, anxiety with the 5-item Beck Anxiety Inventory, and COVID-19 worry on a 5-point Likert-type scale. Cognitive outcomes were assessed with the 6-item Patient Reported Outcomes Measurement Information System (PROMIS®) Cognitive Function and Abilities scales. Marginal structural models incorporating inverse probability of treatment and attrition weights as well as sampling weights estimated the BP and WP relationships between the mental health predictors and PROMIS® cognitive scores over time. Results: In any given month, experiencing a loneliness or anxiety symptom score higher than the sample mean (BP difference) or higher than one's personal mean across the nine-month period (WP change) was negatively associated with cognitive function and abilities in that month. The observed magnitudes of associations were stronger for BP differences than for WP changes and were the strongest for anxiety symptom scale scores. Conclusions: Elevated loneliness and anxiety symptoms, both relative to other adults and to one's usual levels, were acutely associated with worse perceived cognitive function and abilities over a nine-month period during the COVID-19 pandemic in the United States. The long-term impacts of mental health symptoms experienced during the pandemic for population cognitive health should be explored.